Degradation of lignocellulose by different bacterial and fungal co-cultures - Julian Detain; Ludovic Besaury (Current Research in Microbial Sciences)
Long seen as non-valorisable waste, agricultural co-products are increasingly used in biorefinery processes. Co-culture appears as new trend for to improve the degradation of lignocellulose and improve the production of bioproducts. The goal of the study was to setup inter-domain co-cultures with high capabilities of lignocellulose degradation using a pluridisciplinary approach combining bioinformatics, enzymology, transcriptomics. Different individual lignocellulolytic strains: Trichoderma reesei QM6a and three bacteria (Streptomyces coelicolor A3(2), Rhizobium sp.XylPr11 and Sphingobacterium prati AraPr2 affiliated from different phyla) were used in that study . Synergic activities have been observed and quantified in co-culture conditions, particularly for xylanases and peroxidases activities. The enzymatic activities for the co-cultures in the most interesting co-culture (T. reesei QM6a/S. coelicolor A3(2)) reached more up to 2 IU/mL and 430 IU/mL respectively for the xylanase and peroxidase. Furthermore, ATR-FTIR analysis showed a real impact of co-culture condition on the substrate compared to the monoculture specially for hemicellulose degradation. Transcriptomics of S. coelicolor A3(2) either in mono or co-culture showed a relative similar pattern profile whatever the condition analysed with a specific overexpression of certain CAZyme genes involved in glycolysis due to the hydrolytic role played by the fungal partner. This work provided the proof of concept for technological feasibility, pertinence and usefulness of interdomain co-culture.